Population genomics and sexual signals support reproductive character displacement in Uperoleia (Anura: Myobatrachidae) in a contact zone. Issue 17 (22nd July 2022) - Jaya, Frederick R.; Tanner, Jessie C.; Whitehead, Michael R.; Doughty, Paul; Keogh, J. Scott; Moritz, Craig C.; Catullo, Renee A.
Abstract: When closely related species come into contact via range expansion, both may experience reduced fitness as a result of the interaction. Selection is expected to favour traits that minimize costly interspecies reproductive interactions (such as mismating) via a phenomenon called reproductive character displacement (RCD). Research on RCD frequently assumes secondary contact between species, but the geographical history of species interactions is often unknown. Population genomic data permit tests of geographical hypotheses about species origins and secondary contact through range expansion. We used population genomic data from single nucleotide polymorphisms (SNPs), mitochondrial sequence data, advertisement call data and morphological data to investigate a species complex of toadlets ( Uperoleia borealis, U. crassa, U. inundata ) from northern Australia. Although the three species of frogs were morphologically indistinguishable in our analysis, we determined that U. crassa and U. inundata form a single species (synonymized here) based on an absence of genomic divergence. SNP data identified the phylogeographical origin of U. crassa as the Top End, with subsequent westward invasion into the range of U. borealis in the Kimberley. We identified six F1 hybrids, all of which had the U. borealis mitochondrial haplotype, suggesting unidirectional hybridization. Consistent with the RCD hypothesis, U. borealis and U. crassa sexual signals differ more in sympatry than in allopatry. Hybrid males have intermediate calls, which probably reduces attractiveness to females. Integrating population genomic data, mitochondrial sequencing, morphology and behavioural approaches provides an unusually detailed collection of evidence for reproductive character displacement following range expansion and secondary contact.